Fractal regulation and incident Alzheimer's disease in elderly individuals. Issue 9 (4th May 2018) - Li, Peng; Yu, Lei; Lim, Andrew S.P.; Buchman, Aron S.; Scheer, Frank A.J.L.; Shea, Steven A.; Schneider, Julie A.; Bennett, David A.; Hu, Kun
Abstract: Introduction: Healthy physiological systems exhibit fractal regulation (FR), generating similar fluctuation patterns in physiological outputs across different time scales. FR in motor activity is degraded in dementia, and the degradation correlates to cognitive decline. We tested whether degraded FR predicts Alzheimer's dementia. Methods: FR in motor activity was assessed in 1097 nondemented older adults at baseline. Cognition was assessed annually for up to 11 years. Results: Participants with an FR metric at the 10th percentile in this cohort had a 1.8‐fold Alzheimer's disease risk (equivalent to the effect of being ∼5.2 years older) and 1.3‐fold risk for mild cognitive impairment (equivalent to the effect of being ∼3.0 years older) than those at the 90th percentile. Consistently, degraded FR predicted faster cognitive decline. These associations were independent of physical activity, sleep fragmentation, and stability of daily activity rhythms. Discussion: FR may be a useful tool for predicting Alzheimer's dementia.